РЕШЕНИЕ ЗАДАЧ ПРОГНОЗИРОВАНИЯ СОСТОЯНИЯ И УПРАВЛЕНИЯ ЖИЗНЕННЫМ ЦИКЛОМ СЛОЖНЫХ ТЕХНИЧЕСКИХ КОМПЛЕКСОВ МЕТОДАМИ РАСПОЗНАВАНИЯ ОБРАЗОВ - Gennady A. Berketov; Andrei A. Mikrukov; Anatoly P. Tsurkin (Статистика и экономика, 2016)
In article the mathematical model of estimation and forecasting of a condition of difficult technical system based on the use of methods of images recognition is considered. Recognition algorithms based on comparison of the measured vector of signs to the aprioristic description of objects classes’ conditions are offered. The decision on accessory of current object state to one of classes is made by results of recognition algorithms. The developed algorithms can be used as the solution of management problems of difficult technical complexes life cycle.